Practical terrorism prevention reexamining U.S. national approaches to addressing the threat of ideologically motivated violence - Jackson, Brian A. 1972-; Rhoades, Ashley L.; Reimer, Jordan R.; Lander, Natasha ca. 20./21. Jh; Costello, Katherine; Beaghley, Sina (RAND Corporation, 2019)
Terrorism prevention-superseding the programs and activities previously known as countering violent extremism (CVE)-policies seek to broaden the options available to address the risk of individual radicalization and mobilization to ideologically driven violence. These programs provide alternatives to arrest, prosecution, and incarceration by countering recruiting or radicalizing messages, intervening before individuals have committed serious crimes, or supporting the reentry and desistance from violence of individuals convicted and incarcerated for terrorism-related offenses. Government involvement in these programs has been controversial, due to concerns about such efforts' potential to infringe on Constitutionally protected rights and the risk of outreach or intervention activities stigmatizing communities by associating them with terrorism or extremism. The U.S. Department of Homeland Security's (DHS's) Office of Policy requested that the Homeland Security and Operational Analysis Center examine past U.S. CVE and current terrorism prevention efforts, evaluate the DHS and interagency posture for federal efforts, and explore policy options to strengthen terrorism prevention going forward. Researchers found that current terrorism prevention capabilities are relatively limited. Most initiatives are implemented locally or outside government, and only a subset receive federal support. Among interviewees in law enforcement, government, and some community organizations, there is a perceived need for a variety of federal efforts to help strengthen and broaden local and nongovernmental capacity. However, doing so will be challenging, since concerns about past counterterrorism and CVE efforts have significantly damaged trust in some communities. As a result, terrorism prevention policy and programs will need to focus on building trust locally, and designing programs and federal activities to maintain that trust over time.
Place of publication taken from publisher's website
"Does not include Appendixes"
Keywords: Terrorism / United States / Prevention; Radicalism / United States; Violence / United States / Prevention